2017
DOI: 10.1186/s40893-017-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Disease modifying treatments and symptomatic drugs for cognitive impairment in multiple sclerosis: where do we stand?

Abstract: Cognitive dysfunction is frequent in multiple sclerosis patients and has important and negative consequences for daily activities and quality of life of subjects. Disease modifying treatments for multiple sclerosis reduce the incidence of relapses and may prevent disease progression, but the influence on cognitive impairment is unclear, due to several limitations of the available studies. Moreover, symptomatic drugs for the improvement of already established cognitive deficits have been tested in small pilot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…By reducing the inflammation and burden of T1 and T2 brain lesions, disease-modifying therapies may have beneficial effects on cognition [ 36 ]. Several studies have demonstrated protective effects of interferons, glatiramer acetate, fingolimod, and natalizumab on cognitive status [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…By reducing the inflammation and burden of T1 and T2 brain lesions, disease-modifying therapies may have beneficial effects on cognition [ 36 ]. Several studies have demonstrated protective effects of interferons, glatiramer acetate, fingolimod, and natalizumab on cognitive status [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmaceutical agents and supplements used in dementia have not proven to be efficacious in MS (Amato et al, 2013;He et al, 2013) while there is limited evidence to support that diseasemodifying drugs may have an impact on cognitive functions in MS (Niccolai et al, 2017). It has been suggested that physical exercise may be an alternate approach since, at least in the healthy population, there is some evidence of beneficial effects on cognitive functions (Feinstein, 2011;Sandroff, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yet cognition has rarely been the primary outcome in clinical trials, and high-quality studies have often been called for. 1,3,16,17,19,22 Today, there is general agreement that cognitive functioning should be systematically monitored, 1 but knowledge is lacking about MS patients' attitudes towards introducing routine cognitive testing, which is crucial to successful implementation. Exploring patients' views in relapsing and progressive phases on this possibility was therefore the main aim of this qualitative study set in Denmark.…”
Section: Introductionmentioning
confidence: 99%